Effectiveness Of Different Variables On Occupational Commitment Of Bank Employees (Journal of Namibian Studies : History Politics Culture, 2023)
Employee retention, efficiency in the workplace, and overall happiness all depend on a dedicated workforce. Officers in the banking business have unique problems and possibilities, so it's important to learn what motivates them to stay in their jobs. Personal questionnaires were used to compile the data. One hundred officials from several Cochin banks took part in the survey. Participants were limited to individuals who have completed their trial term for the research. The information was analyzed using SPSS version 20. According to the findings, there is a strong connection between several supporting variables and the dedication of bank officials to their organizations. Organizational commitment may be accurately predicted by using any of the components included in the regression.